KOMPOSISI SERANGGA YANG TERDAPAT PADA PERKEBUNAN TEH PTP NUSANTARA VI PERSERO UNIT USAHA DANAU KEMBAR KABUPATEN SOLOK SUMATERA BARAT - Elfina, Ria; i, M. Si, Drs. Ard; Lusi Z, S. Si, M. Si, Armein (Pendidikan Biologi, 2014)
Abbstract:Insecta is a kind of pest which can damage the root, stem, flower and leaf of the tea plant. Related to the case above, this research aims to identify the insectsâ compositions on the tea plantation at PTP Nusantara VI Persero Unit Usaha Danau Kembar Kabupaten Solok. This research used the survey descriptive method by collecting the insects from the observation place directly. It used the chemical Knock Down technique (an insect trap use the chemical substance). The sample was taken twice (a day in a week) as long as two weeks. It was identified at the Biology Laboratory of UNAND which the composition population density, relative, density presence freguensy, relative freguensy is only counted. Besides that, the environmental factos that affect the observation proces such as temperature and humidity were also mesured. Based on the research finding, the insect compositions that have been found by the researcher in the tea plantation of PTP Nusantara VI Persero Unit Usaha Danau Kembar Kabupaten Solok Sumatera Barat are about 8 Ordos, 13 Families, and 14 Genus. The higher relative compactness includes on Genus Scudderia (75 %) and the lower relative compactness involve on Genus Carabus, Malachius, Platinema, Eushistus, Monopa, Tersilochus, (11, 11 %). Furthermore, the average of the temperature are 290C, 270C, 250C, meanwhile the humidity are about 55%,58%, 61%.Â